A new winter common wheat VARIETY ‘Sultan’ - I. D. Fadeeva (Зерновое хозяйство России)
Winter wheat occupies significant areas in the fields of the Republic of Tatarstan. The purpose of the current paper was to develope a new winter common wheat variety ‘Sultan’ and to identify its ability to produce not only high yields, but also grain quality in the conditions of the Republic. The study was carried out on the fields of the TatRIA, a separate structural subdivision of the FRC KazSC RAS on gray forest soil when sown on bare fallow at the optimal time for this area. The paper has presented the characteristics of the variety according to economically valuable traits during the years of study (2018–2020). The variety was developed by the method of individual selection from a hybrid population (Kazanskaya84 х Moskovskaya39) х Kazanskaya 285. According to the productivity, the new variety ‘Sultan’ has exceeded the standard variety ‘Kazanskaya 560’ by 0.75 t/ha. There has been established that the large productivity of the variety ‘Sultan’ is formed due to the density of the productive stem, large number and weight of grain per ear. The variety is characterized by high frost-winter resistance (90 % on average over three years of trials), can withstand a temperature decrease at the level of the tillering node to minus 20°C in winter. The variety has a high reparation ability in spring. The variety ‘Sultan’ forms well-filled grain with a grain unit of 780–801 g/l. Crude protein in grain is of 14.9–15.6 %, and 26.8–28.5 % of gluten. The variety has high values of rheological properties, namely the specific work of dough deformation according to the alveograph (flour strength) is 275 e.u., the valorimetric value is 60 %. On average, over the three years of the study, the volume yield from 100 g of flour was 576 ml3, the general baking assessment was 4.6 points. The variety can be recommended for cultivation in the south-east of the Republic of Tatarstan.